Managerial turnover in a changing world - Daniel Garrett; Alessandro Pavan (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2010)
We characterize a firm's profit-maximizing turnover policy in an environment where managerial productivity changes stochastically over time and is the managers' private information. Our key positive result shows that the productivity level that the firm requires for retention declines with the managers' tenure in the firm. Our key normative result shows that, compared to what is efficient, the profit-maximizing policy either induces excessive retention (i.e., inefficiently low turnover) at all tenure levels, or excessive firing at the early stages of the relationship followed by excessive retention after sufficiently long tenure.
Keywords: D82; 330; managerial turnover; termination clauses; dynamic mechanism design; adverse selection; moral hazard